Circadian variation of essential oil from Piper marginatum Jacq - Marcilio M. MORAES (Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas, 2014)
The composition of the essential oil from the leaves of Piper marginatum (Piperaceae) shows circadian variation and a higher yield during high solar incidence. The essential oils samples were investigated by GC - FID and GC - MS, which allowed identificat ion of 29 compounds. Principal component analysis (PCA) and cluster analysis (CA) showed a significant quantitative variability in the chemical composition of the studied samples as well as a correlation between the oil profiles and the collection time. Tw o main groups were observed, with predominance of phenylpropanoids or sesquiterpenes. The predominant chemical compounds were phenylpropanoids, having as main representative ( Z ) - asarone and ( E ) - asarone.